2022
DOI: 10.3897/natureconservation.47.73036
|View full text |Cite
|
Sign up to set email alerts
|

Speed thrills but kills: A case study on seasonal variation in roadkill mortality on National highway 715 (new) in Kaziranga-Karbi Anglong Landscape, Assam, India

Abstract: Animal-vehicle collision on the roads is a major cause of mortality of a wide range of animal taxa both within and around protected areas. This study has been conducted in the National Highway 715 (new) covering a continuous stretch of 64 km that passes through Kaziranga National Park (KNP) of Assam (India). The area falls between the boundary of KNP on its north and North Karbi Anglong Wildlife sanctuary on the south. The survey concentrated on the mortality study of four groups of vertebrates viz., amphibian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The abundance of the species around roads is among the key factors affecting roadkill status (Dutta 2016). Sur et al (2022), while assessing roadkill on the road passing through Kaziranga tiger reserve, found that the most frequently killed species were the generalist and abundant, like common Indian toad and squirrel species. Our study road has ravines and large trees which act as suitable habitats for common species such as frogs and squirrels, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of the species around roads is among the key factors affecting roadkill status (Dutta 2016). Sur et al (2022), while assessing roadkill on the road passing through Kaziranga tiger reserve, found that the most frequently killed species were the generalist and abundant, like common Indian toad and squirrel species. Our study road has ravines and large trees which act as suitable habitats for common species such as frogs and squirrels, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the foraging nature of frogs and toads, which are very fond of gathering near street lamps and vehicle headlights to feast on insects (Daniels 2005) could be one of the possible reasons for their higher susceptibility to becoming roadkill victims. High roadkill of garden lizards could be due to canopy gap, which forces them to cross the roads and hence the high number of kills (Sur et al 2022). Among reptiles, apart from one species, i.e., the common garden lizard all other kills were of snake species.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a 1496 km survey, they reported 1389 carcasses of 578 amphibians, 540 reptiles, 190 mammals, and 81 birds, which accounted for 1389 carcasses or 0.93 WVCs km -1 . Sur et al (2022) reported the WVCs in Kaziranga National Park, Assam India on a 64 km long highway that passed through it from October 2016 to September 2017. A total of 6036 individual cases of roadkill were registered, belonging to 53 species, 23 other taxa, and 30 families of vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Generalist species such as the crab-eating fox (Cerdocyon thous) and the six-banded armadillo (Euphractus sexcinctus), showed higher roadkill probabilities in human-modified regions; however, habitat specialist mammals, such as the giant anteater (Myrmecophaga tridactyla) and the collared-anteater (Tamandua tetradactyla), showed higher roadkill risk with increasing fragmentation of forest or savanna areas, respectively (Cirino et al 2022). From India, Sur et al (2022) present the first patterns of vertebrate roadkill assessed in a National Park, demonstrating that roadkill rates were highest during the monsoon season, particularly for amphibians. The analysis of long-term mortality of the brown bear (Ursus arctos) in Greece revealed 60% of roadkills were concentrated in four hotspots, occurring most often in periods of increased animal mobility, under poor light conditions and reduced visibility (Psaralexi et al 2022).…”
Section: About This Collectionmentioning
confidence: 99%